Long-shore transport of sediment during August and September on the Terengganu coast - Phillips, R. P. (Universiti Pertanian Malaysia, 1985)
Mengabang Telipot is a slough about 10 km north of Kuala-Terengganu on the east coast of Peninsular Malaysia. Its mouth is normally closed to free exchange of sea water by a sand "wash-over" bar. On 16 August, 1984 the mouth was opened artificially, the slough became tidal, and a delta of sand was formed. The mouth remained open until the end of September. The long-shore current averaged 13 cm/sec toward the north-west. This modified the delta, and eventually led to the closing of the slough mouth. Deposition on the south-east side of the delta made it possible to estimate a volume of long-shore sand transport of250 cu m/day. This is in agreement with other estimates.